2018
DOI: 10.1371/journal.pone.0208537
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a fixed dose combination antiretroviral therapy drug containing tenofovir, emtricitabine and efavirenz is associated with cardioprotection in high calorie diet-induced obese rats

Abstract: HIV-infection, certain antiretroviral drug classes, especially protease inhibitors (PI), and obesity are associated with increased ischaemic heart disease (IHD) risk. However, the effect of PI-free fixed dose combination (FDC) antiretroviral therapy (ART) on hearts exposed to ischaemia-reperfusion injury (I/R) is unknown, particularly in obesity. This is becoming relevant as World Health Organisation guidelines recommend a FDC ART containing (non-) nucleoside reverse transcriptase inhibitors (tenofovir (TDF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The rationale for using the antiretroviral cocktail in this study is based on the fact that this regimen is not only shown to be effective in inhibiting virus replication in the clinical setting ( 25 , 28 30 ) but also have been efficacious in the SIV–macaque model ( 26 , 27 ), as well as the humanized mouse model of HIV-1 infection ( 32 ). According to the US Food and Drug Administration, due to the increased metabolic rates exhibited by rats, the recommended equivalent drug dose should be ~6 times higher than the human dose ( 33 , 34 ). We have followed guidelines for maximum injection volume by species and site location ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for using the antiretroviral cocktail in this study is based on the fact that this regimen is not only shown to be effective in inhibiting virus replication in the clinical setting ( 25 , 28 30 ) but also have been efficacious in the SIV–macaque model ( 26 , 27 ), as well as the humanized mouse model of HIV-1 infection ( 32 ). According to the US Food and Drug Administration, due to the increased metabolic rates exhibited by rats, the recommended equivalent drug dose should be ~6 times higher than the human dose ( 33 , 34 ). We have followed guidelines for maximum injection volume by species and site location ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Group A: nondiabetic control+vehicle (0.5 mL/100 g) Group B: nondiabetic+HAART (98.2 mg/kg b.w oral) Group C: nondiabetic+HAART-AgNPs (24.5 mg/kg b.w i. p) Group D: diabetic control+vehicle (0.5 mL/100 g) Group E: diabetic+HAART (98.2 mg/kg b.w oral) Group F: diabetic+HAART-AgNPs (24.5 mg/kg b.w i. p) Everson et al [33].…”
Section: Induction Of Experimental Type-2 Diabetes Mellitusmentioning
confidence: 99%
“…Groups 4-6 were diabetic rats designated as diabetic control (DC) administered 0.5 ml/100g distilled water p.o., diabetic + Tenofovir (DT) administered 26.8 mg/kg/bw TDF p.o., and diabetic + silver-nanoparticles + tenofovir (DST) administered 6.7 mg/kg TDF-AgNPs i.p. The drug dosage was determined according to Everson et al [33] Induction of Type II Diabetes Mellitus in rats Type 2 diabetes mellitus was induced using the fructose-Streptozotocin (STZ) rat model as described by [34]. Groups 4-6 rats received 10% fructose solution ad libitum for two weeks.…”
Section: Experimental Designmentioning
confidence: 99%